First evidence of microplastic contamination in the tissue and skeletons of the keystone reef-building coral Siderastrea stellata in coastal reefs - Yasmin Barros; Marcelo Oliveira Soares; Alejandro Pedro Ayala; Vasco Stascxa Neto; Tommaso Giarrizzo; Rivelino Martins Cavalcante (Discover Oceans)
Abstract Most studies on microplastics (MPs) in corals have relied on aquarium experiments, with limited field-based data available for many reef regions. This highlights a gap in in situ studies of microplastics in keystone corals, particularly along the tropical southwest Atlantic coast. Therefore, establishing a database on microplastics in corals is essential for effective monitoring. Our short communication presents the identification of MPs in the major reef-building coral Siderastrea stellata Verrill, 1868, in a Southwestern Atlantic coastal reef, and is therefore a pilot study of microplastics in inshore reef corals. Raman spectroscopy was used to analyze the composition of each microplastic captured in two intertidal reefs. We detected MPs in both the tissue and carbonate skeleton on  coastal reefs. The predominant form was filamentous, with polystyrene being the most common MPs. The observed colors were primarily transparent, with some black and blue fragments. Notably, we provide the first field-based record of microplastics in coral skeletons in the SW Atlantic Ocean. These results highlight the importance of studying microplastics in coral reefs, supporting the hypothesis that these ecologically significant areas are global sinks for plastic pollution.